2020
DOI: 10.1103/physrevb.102.125201
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the gapped and Weyl semimetal scenario in ZrTe5 : Insights from an effective two-band model

Abstract: Here we study the static and dynamic transport properties of a low-energy two-band model proposed previously in Martino et al. [PRL 122, 217402 (2019)], with an anisotropic in-plane linear momentum dependence and a parabolic out-of-plane dispersion. The model is extended to include a negative band gap, which leads to the emergence of a Weyl semimetal (WSM) state, as opposed to the gapped semimetal (GSM) state when the band gap is positive. We calculate and compare the zero-and finite-frequency transport proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…(4.1), this Fermi surface averaging is naturally present in the form of the Fermi-Dirac distribution derivative, which in the case of small T ε F restricts the summation over k to the Fermi surface. This condition fails in the low doped semiconductors [51], where a strong temperature dependence of the electron chemical potential completely smears the Fermi-Dirac distribution and its derivative. Since we know the phonon distributions, as well as the electron-phonon matrix elements, we proceed to evaluate Eq.…”
Section: Generalized Drude Formulamentioning
confidence: 99%
“…(4.1), this Fermi surface averaging is naturally present in the form of the Fermi-Dirac distribution derivative, which in the case of small T ε F restricts the summation over k to the Fermi surface. This condition fails in the low doped semiconductors [51], where a strong temperature dependence of the electron chemical potential completely smears the Fermi-Dirac distribution and its derivative. Since we know the phonon distributions, as well as the electron-phonon matrix elements, we proceed to evaluate Eq.…”
Section: Generalized Drude Formulamentioning
confidence: 99%
“…Recently, a tentative minimal model for ZrTe 5 was put forward, based on optical conductivity measurements [24,33,34]. In contrast to a 3D Dirac semimetal model, it features a linear dispersion in two directions and parabolic dispersion in the orthogonal direction.…”
Section: Introductionmentioning
confidence: 99%
“…First, when M = 0 and (ζ , ζ z ) = (0, 0), H(k) reduces to the simplest Dirac semimetal model, which can describe the single DP phase in Na 3 Bi [29] and Cd 3 As 2 [30,31]. The second is the 2D conical model of ZrTe 5 [20][21][22], where only the linear term in the x − y plane and the parabolic term in the z−direction are included. So the model is equivalent to H(k) when ζ = v z = 0 and corresponds to the point of (ζ , ζ z ) = (0, ∞) in the phase diagram.…”
Section: Model and Phase Diagrammentioning
confidence: 99%
“…An optical spectroscopy study pointed out that the Dirac cone was only 2D and put forward a 2D conical model to describe its ground state [20]. The following theoretical studies revealed that the optical conductivities in the 2D conical model exhibit different dependence on the photon frequency along the x− and z−direction, as Re(σ x ) ∝ ω 1 2 and Re(σ z ) ∝ ω 3 2 [21,22].…”
Section: Introductionmentioning
confidence: 99%